2004
DOI: 10.1111/j.1365-2036.2004.01956.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced incidence of gastroduodenal ulcers associated with lumiracoxib compared with ibuprofen in patients with rheumatoid arthritis

Abstract: SUMMARYBackground: Lumiracoxib (Prexige; Novartis Pharma AG, Basel, Switzerland) is a cyclooxygenase-2 selective inhibitor associated with improved gastrointestinal safety compared with nonsteroidal anti-inflammatory drugs, in patients with osteoarthritis. Aim: To compare the gastroduodenal safety of lumiracoxib with ibuprofen and celecoxib in patients with rheumatoid arthritis. Methods: A total of 893 patients with rheumatoid arthritis were randomized to lumiracoxib 400 mg once daily, lumiracoxib 800 mg once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…Nevertheless, Kivitz and colleagues 214 reported significantly more withdrawals for any reason in the lumiracoxib 400-800 mg/day arms than in the celecoxib 400 mg/day arm.…”
Section: Total Withdrawalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Kivitz and colleagues 214 reported significantly more withdrawals for any reason in the lumiracoxib 400-800 mg/day arms than in the celecoxib 400 mg/day arm.…”
Section: Total Withdrawalsmentioning
confidence: 99%
“…Stratified analyses of endoscopic ulcers according to H. pylori status were reported in Novartis Study 0110, 214 and TARGET reported subgroup analyses of POBs and MIs by low-dose aspirin use. None of the identified trials reported subgroup analyses for age, prior GI status or steroid or anticoagulant use.…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…60 Similar reductions in gastrointestinal risk were observed with the newer COX-2 inhibitors valdecoxib, etoricoxib and lumiracoxib. [61][62][63] …”
Section: Use Of Cox-2 Inhibitorsmentioning
confidence: 99%
“…In another celecoxib trial [23], 655 patients with RA were randomly assigned to celecoxib or diclofenac SR for 24 weeks; gastroduodenal ulcers were endoscopically detected in 33 (15.1%) of 218 patients on diclofenac and 8 (3.8%) of 212 patients on celecoxib (p < 0.001). According to a Cochrane Collaboration systematic review, 5 [23,44,45,46,47] endoscopic studies on 2,439 patients comparing celecoxib with nonselective NSAIDs showed a 79% reduction in the relative risk of gastroduodenal ulcers (table 4) [48]. …”
Section: Safety Of Celecoxibmentioning
confidence: 99%